Application of rational emotive behavior therapy in patients with colorectal cancer undergoing adjuvant chemotherapy - Yuxin Liu; Xiaoyan Ni; Rong Wang; Huini Liu; Zifen Guo (Elsevier, 2022)
Objective: This study aimed to explore the effects of our rational emotive behavior therapy (REBT) program on symptoms, anxiety, depression, and sleep state in patients with colorectal cancer (CRC) undergoing chemotherapy. Methods: From October 2020 to May 2021, fifty-six patients with CRC in a hospital in the Hunan Province were randomly divided into an intervention group (n = 28) and a control group (n = 28). The patients in the intervention group completed a 6-week REBT program based on routine nursing care, including four courses: 1) establish a relationship and formulate health files; 2) group communications and study symptom management; 3) continuously provide health knowledge and strengthen healthy behavior; and 4) review the treatment and summary. The control group maintained routine nursing care. The simplified Chinese version of the Memorial Symptom Assessment Scale Short Form (MSAS-SF-SC), the Hospital Anxiety and Depression Scale (HADS), and the Pittsburgh Sleep Quality Index (PSQI) scale were used to investigate and compare the intervention effects of the two groups at baseline (T1, before the intervention), four weeks (T2), and six weeks (T3) after the intervention. Results: The intervention group was significantly improved in symptoms, anxiety, depression, and sleep state, compared with the control group. At T2, MSAS-SF-SC (24.43 ± 4.26 vs.28.07 ± 3.91), symptom distress (17.29 ± 4.04 vs. 19.39 ± 3.59), symptom frequency (7.14 ± 1.51 vs. 8.68 ± 1.42), HADS (13.68 ± 3.38 vs. 15.86 ± 3.79), anxiety (3.89 ± 1.85 vs. 5.18 ± 2.18), and depression (9.79 ± 2.06 vs. 10.68 ± 2.23), showed that the difference between the two groups was statistically significant (P < 0.05). At T3, MSAS-SF-SC (23.89 ± 3.54 vs. 30.14 ± 3.94), symptom distress (17.61 ± 3.52 vs. 21.32 ± 3.57), symptom frequency (6.29 ± 1.49 vs. 8.82 ± 1.47), HADS (11.82 ± 2.57 vs. 16.29 ± 3.13), anxiety (3.21 ± 1.64 vs. 5.61 ± 1.77), and depression (8.61 ± 1.52 vs. 10.68 ± 1.81), showed that the difference between the two groups was statistically significant (P < 0.05). The sleep state of the intervention group was better than the control group at T3, with decreased score of PSQI [4.00 (3.00,8.00) vs. 9.00 (7.00,12.50), Z = −3.706, P < 0.001]. Conclusion: The 6-week REBT program can effectively improve the symptom, anxiety, depression, and sleep state of patients with CRC undergoing chemotherapy, which could as a care plan for patients with CRC who are repeatedly admitted to the hospital for chemotherapy.